2016
DOI: 10.1038/cddis.2016.328
|View full text |Cite
|
Sign up to set email alerts
|

ZNF32 contributes to the induction of multidrug resistance by regulating TGF-β receptor 2 signaling in lung adenocarcinoma

Abstract: Multidrug resistance (MDR) is one of the most important contributors to the high mortality of cancer and remains a major concern. We previously found that zinc finger protein 32 (ZNF32), an important transcription factor associated with cancer in Homo sapiens, protects tumor cells against cell death induced by oxidative stress and other stimuli. We thus hypothesized that ZNF32 might enable the tolerance of cancer cells to anti-tumor drugs because higher ZNF32 expression has been found in cancer tissues and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Moreover, the mouse homologue of the ZNF32 gene, Zfp637, could markedly increase mTERT expression and telomerase activity and maintain telomere length 25 . As we recently reported, ZNF32 contributes to multidrug resistance in lung adenocarcinoma 26 . Because stem cells are predicted to be responsible for tumour resistance and to influence the effects of therapy, and since more mammospheres are observed in breast cancer cells that over-express ZNF32 during suspension culture, we hypothesized that there may be a relationship between ZNF32 and breast cancer stem cell-like properties.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, the mouse homologue of the ZNF32 gene, Zfp637, could markedly increase mTERT expression and telomerase activity and maintain telomere length 25 . As we recently reported, ZNF32 contributes to multidrug resistance in lung adenocarcinoma 26 . Because stem cells are predicted to be responsible for tumour resistance and to influence the effects of therapy, and since more mammospheres are observed in breast cancer cells that over-express ZNF32 during suspension culture, we hypothesized that there may be a relationship between ZNF32 and breast cancer stem cell-like properties.…”
Section: Introductionsupporting
confidence: 57%
“…The intracellular mechanisms regulating breast cancer stem cell-like populations have been gaining attention. The roles of ZNF32 and GPER in mediating proliferation and drug resistance have been recently highlighted 26 , 48 , 49 . However, the role of ZNF32 and GPER in breast cancer stem cell-like properties and their functional significance have remained rather enigmatic.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, another study suggested that high expression of TGFBR2 may be a poor prognostic indicator for overall survival in estrogen receptor α‐negative breast cancer . Li et al also showed that zinc finger protein 32, an important transcription factor associated with cancer, binds to the TGFBR2 promoter and elevates its expression at the mRNA and protein levels, thereby increasing drug resistance in lung cancer. Consistent with this, our results showed that TGFBR2 was highly expressed in rectal cancer cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several experimental studies revealed a role of ZNF281 (C2H2-type) in tumorigenesis and tumour invasion. ZNF281 is involved in two crucial processes in cancer: the DNA damage response (DDR) 62–65 and the epithelial–mesenchymal transition (EMT). ZNF281 expression is increased upon DNA damage induced by drugs in several cancer types.…”
Section: Role Of Znfs In Diseasesmentioning
confidence: 99%